Partial differential equations admitting a given nonclassical point symmetry. Issue 1 (20th May 2020) - Pucci, Edvige; Saccomandi, Giuseppe
Abstract: Given a local one parameter Lie group of transformations G, we determine the most general scalar partial differential equation in (1 + 1)‐independent variables of a given order admitting G as nonclassical symmetry in the Bluman and Cole sense.